Analytical ultracentrifugation : techniques and methods - Scott, David J., 1970-; Harding, S. E. (Stephen E.); Rowe, Arthur J. (RSC Pub., 2005)
Analytical ultracentrifugation has become an increasingly important technique for monitoring the size and shape of biological macromolecules. Analytical Ultracentrifugation: Techniques and Methods contains contributions from experts in the field, bringing together the multitude of developments that have taken place in instrumentation and analysis over the past decade into a single volume. This book covers the latest methods in analysis along with an extensive introduction for the novice user. Analysis methods in both sedimentation velocity and sedimentation equilibrium are discussed at length. Protein, protein/DNA, membrane proteins and polymer systems are also explored, along with software developments and non-ideality.